Testing the effect of cooperative/competitive priming on the Prisoner's Dilemma. A replication study - Belaus, Anabel (2018)
The replicability crisis in psychology demands direct replications to test the reliability of relevant phenomena. Prime-to-behavior effects have been an area under intense scrutiny given its surprising results. However, intuitive unsurprising effects have been mostly neglected, while they may lack robustness as well. In the present study, we focused on an intuitive prime-to-behavior effect in which Kay and Ross (2003) used a 2x2 design to test cooperation/competition priming crossed with an explicit/non-explicit construal of a Prisoner’s Dilemma (PD). They found a stronger assimilation effect of priming when the situational construal anteceded the decision, but we could not reproduce their findings in the present close replication, despite counting on higher power. Even with limitations due to the unavailability lack of original materials, this replication presents evidence that questions the existence of the original finding, and highlights the need for further replications to get a deeper understanding of the hypothesized effect.